Palm Ant Sugar Management Technology and Its Potential as Souvenirs from Belirang National Tourism Village - Sumartono, Eko; Prasetya, Andwini; Moulina, Methatias Ayu; Taufan, Muhamad (CV. Media Digital Publikasi Indonesia, 2023)
Belitar Seberang Village is a village that has various agricultural and plantation crops that can be found in every area of ​​the village. Plantation crops are dominated by palm or aren (Arengan piñata) plants. Palm sugar (King Aren) in powder form is a natural sweetener made from pure sap water, has a distinctive taste and aroma, is beneficial for health and can be added to coffee, tea and other drinks. The targets of this community service activity are: 1. education and training programs through socialization of Local Commodity-Based Product Development Innovations as Typical Souvenirs from Belirang Tourism Village, 2. Information on packaging materials and forms that can make products last for a long time (etiquette), 3. Design and labeling. 4. Packaging training that attracts consumer interest. 5. Sharing information on effective product marketing methods. The approach taken by the proposer and partners together establishes a vision and mission that can be a solution to partner problems, including through an approach by synergizing activities based on the use of existing resources (socialization and training).